Control of donor-like effect in V2VI3 polycrystalline thermoelectric materials. (March 2018) - Hu, Lipeng; Guo, Yangming; Li, Junqin; Ao, Weiqin; Liu, Fusheng; Zhang, Chaohua; Li, Yu; Zeng, Xierong
Graphical abstract: Highlights: Thermal control of donor-like effect for V2 VI3 polycrystalline materials is proposed. Low-temperature sintering or hot deforming facilitates the donor-like effect. Recovery role by high-temperature sintering/deforming enhances the Seebeck coefficient. Temperature should be strictly selected for each V2 VI3 polycrystalline material. Abstract: Intrinsic point defect plays a core role in improving thermoelectric performance of V2 VI3 polycrystalline materials. However, the control of intrinsic point defect is challenging during powder refinement due to the donor-like effect. This paper shows a systematic approach to thermal control the donor-like effect via engineering spark plasma sintering and hot deformation temperature. Bi2 Te2.85 Se0.15 polycrystalline alloy with high electron concentration was chosen as example to validate the method. The low Seebeck coefficient of n -type Bi2 Te2.85 Se0.15 polycrystalline, arising from strong donor-like effect after powder refinement, was enhanced by recovery role induced reduction in electron concentration through proper tuning sintering or deforming temperature. Repetitive hot deformation was applied to further improve the Seebeck coefficient via the recovery role and a maximum zT of 1.0 is obtained at 410 K. The present results give insights into developing higher performance V2 VI3 polycrystalline materials through thermal control the donor-like effect.